Pengaruh Pemberdayaan Karyawan dan Keterlibatan Kerja terhadap Kinerja Karyawan dengan Kepuasan Kerja sebagai Variabel Intervening pada Klinik Mata Tritya Surabaya - Aprilia, Fina; Mujanah, Siti; Fianto, Achmad Yanu Alif (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
One of the things that can improve performance is employee job satisfaction. This study investigates the effect of employee empowerment and work engagement on employee satisfaction. It also investigates whether employee satisfaction is a good mediator. This study conducted a survey on employees at Tritya Eye Clinic Surabaya. Using saturated sampling method, 66 employees were surveyed. The data was then analyzed using Structural Equation Modeling. The findings show that employee empowerment and work engagement contribute positively to employee satisfaction. The study also proved that employee satisfaction mediates the relationship between employee empowerment and work engagement on employee performance. This study contributes to understanding employee behavior using the framework of employee satisfaction and employee performance at Tritya Eye Clinic Surabaya, which can also be applied to other general companies.